(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objectives: Analyze the cost of maternity and childbirth services package and evaluate the package at Tam Anh General Hospital. Research objects and methods: This is a cross-sectional study, using a semi-structured questionnaire to interview pregnant women who used maternity and childbirth services package at Tam Anh General Hospital from December 2023 to May 2024. Results: The average cost of maternity and childbirth services was 45,532,846 ± 14,318,990 VND, of which the average cost in the package was 35,293,286 ± 8,516,586 VND, the average cost outside the package was 10,239,560 ± 12,078,880 VND. The study showed that the percentage of pregnant women who evaluated the cost of maternity and childbirth services package at Tam Anh General Hospital as reasonable was 88.7%. Factors related to the assessment of the reasonableness of the maternity and childbirth services package included: pregnancy status, method of delivery and length of stay. Conclusions: The cost of the maternity package at Tam Anh General Hospital is higher than some private hospitals in Hanoi. However, the majority of pregnant women who used the maternal and childbirth services package evaluate the cost of the package as reasonable.